Challenges of the implementation of the concept of flexible use of airspace in the Republic of Serbia - Elenkov, Milan P.; Beriša, Hatidža A.; Barišić, Igor I. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The authors analyze the implementation of the concept of flexible use of airspace in the Republic of Serbia, which deals with problems related to airspace capacity. The problem of airspace capacity and air traffic that takes place in it was not seriously considered in Europe before the Second World War, due to the simple fact that the number of flights in that period was relatively small. Achieving this goal and solving the problem is being sought in a better organization of the airspace of Europe, which directly influences the organization and strategy of the development of the airspace of all countries in Europe and the Republic of Serbia (as a signatory and a member of international organizations dealing with traffic management and airspace organization ). The concept of flexible use of airspace should provide a solution to this problem. The implementation of the concept requires some legal and organizational solutions, so a wider national concept is needed for a consistent implementation of the concept. The problems encountered by the creators of the concept in Europe and Serbia and the solutions that have been made are the subject of this paper. The content of the paper is presented through several questions to give an overview of the problem of airspace capacity and an increase expected in the upcoming period. The paper also deals with the division of airspace in the world and in our country; planning, registering and announcing flights; the concept of flexible use of airspace; and the problems of applying the concept in Serbia.